Entre livros, leitura e biblioteca : a inter-relação com o planejamento institucional - Campos, Aura Santana (2020)
The University Library is an essential space in the process of academic education, contributing for the personal and professional growth of the students and inserting them in the universe of education and research. Thus, assuming that reading is fundamental for academic education, and the library is constituted by excellence as a propitious space for this practice, it is intended with this research to contribute with the debate on the planning used in the definition of public resources invested in the acquisition of the bibliographical archive. This research is linked to the Research Group Alphabetization and School Literacy (ALFALE), of the Postgraduate Program in Education, of the Institute of Human and Social Sciences, of the Federal University of Mato Grosso University Campus of Rondonópolis (PPGEdu/CUR/UFMT), in the research line Languages, Culture and Construction of Knowledge: historical and contemporary perspectives. In order to align this research, the following question was formulated: Is there a relation between the demands of the courses of the University Campus of Rondonópolis (CUR) in the acquisition of books to compose the archive of the Regional Library and the corresponding use by part of the academics? The main objective was to analyze the relation between the demand, acquisition and loan of the books that compose the archive of the Regional Library of the University Campus of Rondonópolis. Therefore, the following specific objectives were established: 1) verify the criteria for acquisition and actualization of the archive, considering the adopted policies, the budget, the planning for the acquisition and maintenance of books for the Regional Library of the University Campus of Rondonópolis; 2) relate the quantitative and the cost of the archive acquired in the period of 2014 and 2018; 3) verify the flow of loan of the titles acquired in the period of 2014 and 2018. Based on the proposed objectives, it was opted for utilizing the qualitative and quantitative approaches, integrating them in the moment of the interpretation of the data, in addition, it was employed the research of the type descriptive analytic. It is a study case focused on the Regional Library of the University Campus of Rondonópolis, conducted with the analysis of the reports offered by the Regional Library (BR) and through interviews with the supervisor of the library. The data reveals that in the analyzed period the investment in the BR exceeded the value of a million of real currency. However, in spite of having available a considerable bibliographical archive, the average of loans is little expressive. Therefore, it is evident the necessity of adopting strategies so that the BR fulfills with efficiency its role in the support to the users. In this perspective, planning becomes an indispensable tool so that the administrators identify the weak and strong points of the institution and, with this diagnosis, trace goals, redefine strategies and develop actions, viewing the constant improvement in the administration of the received resources, so that the basic necessities of the activities of education, research and extension be fulfilled.